Pore size dependent molecular adsorption of cationic dye in biomass derived hierarchically porous carbon. (1st July 2017) - Chen, Long; Ji, Tuo; Mu, Liwen; Shi, Yijun; Wang, Huaiyuan; Zhu, Jiahua
Abstract: Hierarchically porous carbon adsorbents were successfully fabricated from different biomass resources (softwood, hardwood, bamboo and cotton) by a facile two-step process, i.e. carbonization in nitrogen and thermal oxidation in air. Without involving any toxic/corrosive chemicals, large surface area of up to 890 m 2 /g was achieved, which is comparable to commercial activated carbon. The porous carbons with various surface area and pore size were used as adsorbents to investigate the pore size dependent adsorption phenomenon. Based on the density functional theory, effective (E-SSA) and ineffective surface area (InE-SSA) was calculated considering the geometry of used probing adsorbate. It was demonstrated that the adsorption capacity strongly depends on E-SSA instead of total surface area. Moreover, a regression model was developed to quantify the adsorption capacities contributed from E-SSA and InE-SSA, respectively. The applicability of this model has been verified by satisfactory prediction results on porous carbons prepared in this work as well as commercial activated carbon. Revealing the pore size dependent adsorption behavior in these biomass derived porous carbon adsorbents will help to design more effective materials (either from biomass or other carbon resources) targeting to specific adsorption applications. Graphical abstract: Highlights: A green process was developed to convert biomass into hierarchically porous carbon. Quantification method was proposed to calculate effective surface area. Effective surface area-adsorption capacity relation was quantitatively correlated. A simplified model was built and verified to precisely predict adsorption capacity.